Selective rearrangement of terminal epoxides into methylketones catalysed by a nucleophilic rhodium-NHC-pincer complex - Jürgens, Eva; Rominger, Frank (Chemical communications, 2015)
An efficient RhI-NHC-pincer catalyst for the highly regioselective Meinwald rearrangement of monoalkylated epoxides into methylketones under mild conditions is presented. The nucleophilic epoxide opening is assisted by Lewis acids.